Dermatological Toxicity of Hydroxycarbamide - IN Subortseva; AL Melikyan; EA Gilyazitdinova; TI Kolosheinova; EI Pustovaya; EK Egorova; AM Kovrigina; AB Sudarikov; AO Abdullaev (Клиническая онкогематология)
Hydroxycarbamide is an antitumor agent mainly used for treatment of Ph-negative myeloproliferative disorders and sickle cell disease. The development of skin ulcers is a rare but serious adverse event in long-term antitumor therapy. Hydroxycarbamide-induced ulcers are often multiple and bilateral, and usually occur in the lower legs, although they can occur in other regions of the body. The ulcers are small-sized and shallow with sharp margins and yellow fibrine-covered base. They cause constant severe, difficult to treat pain which is a characteristic sign. The drug withdrawal usually leads to spontaneous healing of ulcers. Regular dermatologic screening must be obligatory for all the patients receiving hydroxycarbamide. The present paper provides a literature review on dermatological toxicity of hydroxycarbamide and a clinical case description.